Eksistensi Badan Layanan Umum Sebagai Penyelenggara Pelayanan Publik - Henny Juliani (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2018)
This study aims to determine the existence of public service agencies as public service providers in Indonesia. The research method used is legal research with statutory approach approach (analytical approach) which is analyzed with qualitative analysis. The results of the research show that the Public Service Agency (BLU) as the public service provider plays an important role in providing services to the public in the form of the provision of goods and / or services. Legally BLU is not a legal entity, but BLU operates as a working unit of state ministries / agencies / local governments for the purpose of providing public services whose management is based on the authority delegated by the respective parent agency. Therefore, the financial management is not separate from the state ministries / institutions / local government as the parent institution. Keywords: Public Service Board, Public Service, State Organizer